2019
DOI: 10.1155/2019/8561380
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Evaluation of Mobile-Phone Camera Images for 3D Information

Abstract: This study aimed to investigate the usability of smartphone camera images in 3D positioning applications with photogrammetric techniques. These investigations were performed in two stages. In the first stage, the cameras of five smartphones and a digital compact camera were calibrated using a calibration reference object, with signalized points having known three-dimensional (3D) coordinates. In the calibration process, the self-calibration bundle adjustment method was used. To evaluate the metric performances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…The model produced by photogrammetry was of higher quality than the Tango-based one. In [54] the authors concluded that it is possible to obtain high-quality results from numerous images of building captured by smartphone cameras using appropriate software solutions. Very similar results were gained in [55], comparison of riverbank models from TLS and close-range photogrammetry resulting in RMSE from 0,02-0,05 m, depending on the device used (digital single-lens camera x smartphone).…”
Section: Discussionmentioning
confidence: 99%
“…The model produced by photogrammetry was of higher quality than the Tango-based one. In [54] the authors concluded that it is possible to obtain high-quality results from numerous images of building captured by smartphone cameras using appropriate software solutions. Very similar results were gained in [55], comparison of riverbank models from TLS and close-range photogrammetry resulting in RMSE from 0,02-0,05 m, depending on the device used (digital single-lens camera x smartphone).…”
Section: Discussionmentioning
confidence: 99%
“…Digital cameras are applied extensively to the architecture and cultural heritage domain, showing multiple applications [94]. There are various types of research regarding their acquisition performances, mainly referring to mobile phones [95], analyzing optical/geometric capacities [96]. Tracking systems are treated extensively in [1,49], focusing more on markerless systems in [97].…”
Section: Cameras and Tracking Devicesmentioning
confidence: 99%
“…However, in recent years, there has been a great evolution in the technologies related to the acquisition and storage of images on mobile devices, making these low‐cost cameras a possibility for qualified measurements, as discussed in Section 2. The quality of the mobile phone camera can (and should) be measured through quality assessments, as proposed by Ying, Pan, and Shi (2020) and by Yilmazturk and Gurbak (2019).…”
Section: Use In Courtmentioning
confidence: 99%